Explaining the effect of the level for some vital Indicators in people with DM2 and comparing them with healthy people - Elaaf Ali Hussen Ali; Akrm Abd Farhan (Genius Publishing Group, 2025)
The work of collecting samples began from 11/13/2024 from Shirqat General Hospital, Salah al-Din Governorate until 2/14/2025, The study included collecting (50) samples from the people of Sharqat city, and these samples included (40) samples of people with type 2 diabetes and (10) samples of individual person who were considered as a healthy people. The study showed through the results that there is a significant increase (P≤0.05) in the level of urea concentration (45.7±6.2) mg/dl In patients with DM2 when compared with healthy individuals (29.7±4.1). The study showed through the results that there is a significant (P≤0.05) increase of creatinine concentration level (0.95±0.21) mg/dl in the in patients with DM2 when compared with healthy individuals (0.27±0.33). There were no differences significantly (P≤0.05) in the level of total protein concentration (8.2±1.34) g/dl in people with DM2 when compared with healthy individuals (7.3±0.97)
Keywords: DM type 2; Urea; Creatinine